Aplicações do método de indução matemática à geometria - VELOZO NETO, Raimundo do Nascimento (2017)
This work deals with the Method of Mathematical Induction, in particular, its use with a view to the solution of geometric problems. It initially some considerations are made about the expression "inductive reasoning" whose it meaning, as appropriately must be explained in the text, that differs from that of "mathematical induction". We prove the proposition that guarantees the use of the method based on its foundation, namely the axiom of mathematical induction (one of the postulates that characterize the natural numbers). It exhibited some examples of its use of Algebra and the Theory of Numbers. And then, some applications of the method of mathematical induction to the problems of Geometry are explored to obtain a geometric measure in terms of another(s), either for the demonstration of a proposition that insinuates itself true, or for the stages of construction of a figure given